Dependence of progeny abundance for summer chum salmon (Oncorhynchys keta) in the Amur River on the parents abundance - Vladimir I. Ostrovsky; Olga V. Vershinina; Andrey P. Shmigirilov (Известия ТИНРО, 2016)
For almost the century the landings of summer chum salmon in the Amur were approximately in 5 times lower that the landings of fall chum salmon, in spite on almost the same fishing efforts. However, its catches were very high in the 1990-2000s, even higher that for the fall chum salmon, that contradicts to conceptions on its lower absolute fecundity, smaller spawning grounds, and higher vulnerability of its reproduction on unfavorable external factors. Relationship of mature progeny abundance for summer chum salmon with number of their parents is analyzed. The data on the parents and progeny abundance were calculated from fishery statistics, including cited data, considering annual catch as 50 % of the stock. The highest recruitment of summer chum salmon is estimated as 19.08 · 106 ind. that is comparable with the strength of the fall chum salmon year-classes. The spawning stock of 1.94 · 106 ind. is enough to produce this progeny, but the population growth is much lower with the lower spawning stock, that is a real reason for slow recovery of the summer chum salmon stock, though potentially both races could be equally abundant. To maintain the stock of summer chum salmon at the highest level, an optimal number of parents should be passed to the spawning grounds, within rather narrow range, that is difficult to control in conditions of the big river.